Magneto-Compound Reaction of Convective Flow via a Porous Inclined Plate with Heat Energy Absorption (Journal of Nonlinear Modeling and Analysis, 2024)
The current study is concerned with the unsteady heat and masstransfer of MHD free convection flow via a porous inclined plate that accelerates exponentially with temperature and concentration. Heat emission,source/sink, radiation absorption, and reaction are taken into account in theenergy and species equations. The innovative part of the work is the analysisof the flow phenomenon with a heat source or sink and radiation absorptionalong the chemical reaction. The governing PDEs are reduced into ODEs viathe non-dimensional variables and afterward solved analytically utilizing theperturbation strategy. Graphical representations of liquid temperature, speed,and concentration as well as the Sherwood & Nusselt quantities and the skinfriction factor are displayed in tabular form for different combinations of appropriate stream quantities. The analysis of a resistance quantum grows withthe size of the magnetic, whereas the rates of mass and heat transfer declinewith increasing radiation, reaction, and Schmidt number. Thermal-velocityand concentration-velocity profiles interact reciprocally with the acceleratingradiation, heat source, and compound reaction. The growth of speed and thermal profiles is clearly visible due to the absorption and Prandtl values. Thepresent results are in strongly consistent with the earlier published results.There are numerous applications for this research in many sectors and material processing for understanding drag in seepage flows on heated/cooled andinclined surfaces.
Keywords: Convection Flow; MHD; porous medium; chemical reaction; inclined plate; radiation.